Efficacy Evaluation of Different Mineral Clay Particles on Olive Production Traits and Olive Oil Quality of ‘Koroneiki’ Olive Cultivar Under Rainfed and Irrigated Conditions in Southern Greece - Petros Anargyrou Roussos; Asimina-Georgia Karyda; Panagiotis Kapasouris; Panagiota G. Kosmadaki; Chrysa Kotsi; Maria Zoti (Horticulturae)
Climate crisis in the Mediterranean region has severely affected olive tree cultivation, especially due to the long, dry summers, when temperature often rises above 40 °C. In order to overcome such climate challenges in the olive sector, the particle film technology (PFT) was used, as an environmentally friendly alleviation technique, due mainly to the reflecting properties of clay materials. Three clay materials—attapulgite, talc, and kaolin—were applied foliarly to olive trees (both rainfed and irrigated) in July and August. At harvest, yield and oil production per tree were assessed, alongside olive oil quality and functional properties. Under irrigated conditions, trees treated with kaolin or talc in July exhibited the highest yields, whereas under rainfed conditions, trees treated with attapulgite in August, followed by those treated with talc in August, showed the greatest yields. Oil production exceeded that of controls in rainfed trees across nearly all clay treatments. Oils from irrigated trees treated with talc in August and rainfed trees treated with talc in July exhibited high phenolic content, though antioxidant capacity peaked in oils from trees treated with talc in August. These oils, along with those from trees treated with attapulgite in August, contained the highest concentrations of hydroxytyrosol and oleacein. In rainfed trees, most clay treatments resulted in oils with elevated oleic acid (C18:1) and reduced linoleic acid levels, yielding a high monounsaturated-to-polyunsaturated fatty acid ratio. In irrigated groves, August applications produced oils with distinct differences from controls, whereas in rainfed conditions, these differences were evident regardless of application timing. Clay materials offer a promising approach for mitigating abiotic stress under Mediterranean summer conditions; however, further research is needed to elucidate their mechanisms of action. This study represents the first report of foliar attapulgite application in plants and talc application in olive trees.